Roles of M2 and M3 muscarinic receptors in the generation of rhythmic motor activity in mouse small intestine. Issue 10 (28th July 2013) - Tanahashi, Y.; Waki, N.; Unno, T.; Matsuyama, H.; Iino, S.; Kitazawa, T.; Yamada, M.; Komori, S.
Abstract Background The roles of M2 and M3 muscarinic receptor subtypes in the regulation of gut motor activity were investigated. Methods We simultaneously recorded changes in the intraluminal pressure (IP) and longitudinal tension (LT) in small intestinal segments from M2 or M3 receptor knockout (KO) and wild‐type (WT) mice. Key Results In the WT preparations, luminal distension induced a continuous rhythmic contractile activity that was characterized by synchronous rises in IP and LT, occurring periodically at a constant interval. Tetrodotoxin completely abolished the response, whereas atropine either abolished or attenuated it. In the majority of the M2KO preparations, however, no rhythmic activity was observed in response to the luminal distention, even though networks of enteric neurons and interstitial cells of Cajal (ICC) seemed to be intact. Where rhythmic activity did occur in M2KO preparations, it was atropine resistant. In the M3KO preparations, the IP and LT were synchronously changed by the luminal distention, but the changes occurred at irregular intervals. The W/Wv mutant preparations, which lack ICC in the myenteric plexus (ICC‐MY), showed results similar to those of the M3KO preparations. In some of the M2/M3 double‐KO preparations, rhythmic activity was not observed, but in the others, an atropine‐resistant rhythmicity appeared. Conclusions & Inferences These results suggest that M2 and M3 muscarinic receptors differentially regulate the intestinal motor activity: M2 receptors play an essential role in the generation of rhythmic motor activity, and M3 receptors have a modulatory role in controlling the periodicity of the rhythmic activity together with the ICC‐MY.